2017
DOI: 10.1159/000480140
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Fibrosis and Activity by a Combined Use of Strain and Shear Wave Imaging in Patients with Liver Disease

Abstract: Objective: Performing shear wave imaging is simple, but can be difficult when inflammation, jaundice, and congestion are present. Therefore, the correct diagnosis of liver fibrosis using shear wave imaging alone might be difficult in mild-to-moderate fibrosis cases. Strain imaging can diagnose liver fibrosis without the influence of inflammation. Therefore, the combined use of strain and shear wave imaging (combinational elastography) for cases without jaundice and congestion might be useful for evaluating fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 33 publications
1
34
0
2
Order By: Relevance
“…Furthermore, it has been reported that liver fibrosis correlates with the prognosis of chronic hepatitis including NAFLD; thus, assessment of liver fibrosis is also essential . In the present study, we used an ultrasonic system that diagnoses liver fibrosis using a combination of strain and shear wave imaging, and reported the utility of its diagnostic capability for liver fibrosis . Moreover, it is possible to undertake simultaneous diagnosis of B‐mode imaging, liver steatosis, and fibrosis using the same device, which is considered to be a unique advantage not established in other equipment.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, it has been reported that liver fibrosis correlates with the prognosis of chronic hepatitis including NAFLD; thus, assessment of liver fibrosis is also essential . In the present study, we used an ultrasonic system that diagnoses liver fibrosis using a combination of strain and shear wave imaging, and reported the utility of its diagnostic capability for liver fibrosis . Moreover, it is possible to undertake simultaneous diagnosis of B‐mode imaging, liver steatosis, and fibrosis using the same device, which is considered to be a unique advantage not established in other equipment.…”
Section: Discussionmentioning
confidence: 92%
“…The SWM device has a unique reliability index, the VsN, which is used to determine whether the Vs value is reliable. Yada reported that a VsN ≥ 50% could be a good indicator of accurate SWM in the liver [10, 11]. Using this index, data can be collected with high reliability.…”
Section: Discussionmentioning
confidence: 99%
“…1). Using the reliability index, the percentage of the net amount of effective shear-wave velocity (VsN: %) was calculated to determine whether shear-wave propagation was detected correctly and whether unnecessary components other than those generated by shear-wave propagation existed in the ROI according to predefined rejection conditions, and the value was displayed on the monitor [10, 11]. EUS-SWMs of the pancreatic body and tail were performed through the stomach, and measurements of the pancreatic head were performed through the duodenum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pSWE was combined with strain elastography on a Hitachi system. A study evaluated 388 patients with this combined technique, considering liver biopsy as reference method [76]. The AUROCs to predict fibrosis stage were 0.87, 0.80, 0.83, and 0.80 for F1, F2, F3, and F4, respectively, while the AUROCs for activity grade were 0.94, 0.74, and 0.76 for A1, A2, and A3, respectively.…”
Section: Point Shear-wave Elastography (Pswe): Perspectivesmentioning
confidence: 99%